设 $X_1, X_2, \cdots, X_n$ 为来自总体 $N\left(\mu_1, \sigma^2\right)$ 的简单随机样本, $Y_1, Y_2, \cdots, Y_m$ 为来自总体 $N\left(\mu_2, 2 \sigma^2\right)$ 的简单随机样本, 且两样本相互独立, 记 $\bar{X}=\frac{1}{n} \sum_{i=1}^n X_i$, $\bar{Y}=\frac{1}{m} \sum_{i=1}^m Y_i, \quad S_1^2=\frac{1}{n-1} \sum_{i=1}^n\left(X_i-\bar{X}\right)^2, \quad S_2{ }^2=\frac{1}{m-1} \sum_{i=1}^m\left(Y_i-\bar{Y}\right)^2$, 则
$ \text{A.} $ $\frac{S_1^2}{S_2^2} \sim F(n, m)$ $ \text{B.} $ $\frac{S_1^2}{S_2^2} \sim F(n-1, m-1)$ $ \text{C.} $ $\frac{2 S_1^2}{S_2^2} \sim F(n, m)$ $ \text{D.} $ $\frac{2 S_1^2}{S_2^2} \sim F(n-1, m-1)$
【答案】 D

【解析】 $X_1, X_2, \ldots, X_n$ 的样本方差 $S_1^2=\frac{1}{n-1} \sum_{i=1}^n\left(X_i-\bar{X}\right)^2$,
$Y_1, Y_2, \ldots, Y_n$ 的样本方差 $S_2^2=\frac{1}{m-1} \sum_{i=1}^m\left(Y_i-\bar{Y}\right)^2$, 则 $\frac{(n-1) S_1^2}{\sigma^2} \sim \chi^2(n-1)$,
$\frac{(m-1) S_2^2}{2 \sigma^2} \sim \chi^2(m-1)$, 两个样本相互独立,
所以 $\frac{\frac{(n-1) S_1^2}{\sigma^2} /(n-1)}{\frac{(m-1) S_2^2}{2 \sigma^2} /(m-1)}=\frac{S_1^2 / \sigma^2}{S_2^2 / 2 \sigma^2}=\frac{2 S_1^2}{S_2^2} \sim F(n-1, m-1)$,
故选(D).
系统推荐